Knowledge management strategic context in technological trajectories of firm influences their innovation strategy: Looking at Malaysian multinational firm - Mohd Nawi, Mohd Nasrun; Ahmad Zaidi, Muhammad Faisal; Azmi, Azwan Iskandar; Ibrahim, Amlus; Ramayah, T. (Universiti Utara Malaysia, 2006)
The paper study on the knowledge management strategic context in technological trajectories of firm influences their innovation strategy. Thus, to make use of technology as a competitive weapon; managers must manage it as a part of the business system. Failure to develop and integrate technology strategy and business is a major contributing factor in the decline of a firm's competitiveness In a turbulent and rapidly changing environment, every organization faces the challenge of how to best manage its knowledge assets to generate value for the market place and obtain competitive advantage Such advantage derives from special capabilities that are rare, valuable, nonsubstitutable, and costly to imitate. Historically, the focus was on capabilities involving tangible assets; now, knowledge is widely recognized as the source for competitive advantage, with the tangible assets representing the physical manifestation of but a fraction of this knowledge As companies scramble to develop strategies for more proactively and strategically managing their knowledge, the field of knowledge management (KM) receives increasing attention from trade organizations and academic journals. From this study it was found that to improve the chances of conclusively demonstrating value to the K-Economy, a new KM implementation in an innovation organization should address issues such as organization's goals and strategies, access tacit knowledge, provide search tools, promote creativity, capture new learning and build a supportive culture,insufficient communication, failure to integrate knowledge, lack of time to learn, lack of training a senses there was little personal benefit in knowledge management.